Arguing for atheism : an introduction to the philosophy of religion - Le Poidevin, Robin, 1962- (Routledge, 1996)
In Arguing for Atheism, Robin Le Poidevin addresses the question of whether theism - the view that there is a personal, transcendent creator of the universe - solves the deepest mysteries of existence. Philosophical defences of theism have often been based on the idea that it explains things which atheistic approaches cannot: for example, why the universe exists, and how there can be objective moral values. The main contention of Arguing for Atheism is that the reverse is true: that in fact theism fails to explain many things it claims to. Such an interpretation has been argued for recently by 'radical theologians'; Arguing for Atheism is therefore, a philosophical contribution to one of the key religious issues of our times. Designed as a text for university courses in the philosophy of religion and metaphysics, this book's accessible style and numerous explanations of important philosophical concepts and positions will also make it attractive to the general reader.